Repurposing Etalocib suppresses multidrug-resistant Staphylococcus aureus by disrupting the bacterial membrane - Xuancheng Huang; Congcong Li; Chaoqin Zhang; Yong Xiang; Zhijian Yu; Peiyu Li; Bing Bai; Zewen Wen; Tieying Hou (BMC Microbiology)
Abstract Background The emergence of multidrug-resistant (MDR) Staphylococcus aureus (S. aureus) seriously poses a serious threat to human health and presents a significant clinical challenge. Therefore, it is urgent to explore alternative treatments and develop novel antimicrobial agents. To investigate the antibacterial activity of Etalocib against S. aureus and elucidate its underlying mechanism of action. Results Etalocib, a drug previously investigated in clinical trials, exhibited notable antibacterial activity against S. aureus, with a minimum inhibitory concentration (MIC) of ≤ 25 μM. Time-kill curves demonstrated concentration-dependent bactericidal effects. Etalocib could significantly inhibited biofilm formation and kill bacteria within mature biofilms. Moreover, permeability assays revealed that Etalocib treatment caused bacterial membrane damage, accompanied by dissipation of membrane potential. Checkerboard analysis showed that bacterial membrane phospholipids, including phosphatidylglycerol and cardiolipin, could neutralize the antibacterial activity of Etalocib in a dose-dependent manner. These findings suggest that the primary mechanism of action involves disruption of the bacterial membrane, potentially through interactions with membrane phospholipids, alterations in protein homeostasis, and disturbances in energy and metabolic processes. Notably, Etalocib significantly improved the survival rate of the Galleria mellonella in the methicillin-resistant S. aureus (MRSA) infection model. Conclusions The findings highlight the potential of Etalocib as an effective antibacterial agent for combating MDR S. aureus infections. It holds significant promise as a novel therapeutic option for the treatment of severe infections caused by Gram-positive pathogens.